Time trends in cardiovascular disease mortality in Russia and Germany from 1980 to 2007 - are there migration effects? - Deckert, Andreas; Winkler, Volker; Paltiel, Ari M.; Razum, Oliver; Becher, Heiko (BMC public health, 2010)
BACKGROUND: Cardiovascular disease (CVD) is the leading cause of death in the industrialized world. Large variations in CVD mortality between countries and also between population subgroups within countries have been observed. Previous studies showed significantly lower risks in German repatriates and Jews emigrating from Russia than in the general Russian population. We examined to what degree the migration of large subgroups influenced national CVD mortality rates. - METHODS: We used WHO data to map the CVD mortality distribution in Europe in 2005. Supplemented by data of the Statistisches Bundesamt, the mortality trends in three major CVD groups between 1980 and 2007 in Russia and Germany are displayed, as well as demographic information. The effects of migration on demography were estimated and percentage changes in CVD mortality trends were calculated under the assumption that migration had not occurred. - RESULTS: Cardiovascular disease mortality patterns within Europe showed a strong west-east gradient with ratios up to sixfold. In Germany, the CVD mortality levels were low and steadily decreasing, whereas in Russia they fluctuated at high levels with substantial differences between the sexes and strong correlations with political changes and health campaigns. The trends in both Russia and Germany were affected by the migration that occurred in both countries over recent decades. However, our restricted focus in only adjusting for the migration of German repatriates and Jews had moderate effects on the national CVD mortality statistics in Germany (+1.0%) and Russia (-0.6%). - CONCLUSIONS: The effects on CVD mortality rates due to migration in Germany and Russia were smaller than those due to secular economical changes. However, migration should still be considered as a factor influencing national mortality trends.
Gesehen am 20.10.2023